De la sociabilité à la pudeur : l’éthique des larmes au xviiie siècle - Hakim, Zeina (Lumen, 2021)
The eighteenth century occupies a crucial place in the history of tears. Not only did this period gave rise to the concept of sensibility, but it also witnessed the development of new aesthetic and moral codes founded on the exaggerated use of tears. This article, which is concerned precisely with such codes, examines the nature and significance of emotional display in the eighteenth century. It argues that throughout this era, tears were associated with moral renewal and they were intended to be shared, particularly when engendered on the theatre stage. This study also shows how these collective tears were steadily devalued as a public good throughout the nineteenth century, to the point that the act of weeping became personal and intimate, valorizing the individual instead of the communal.